REPATRIATION ADJUSTMENT OF ACADEMICS: IS COWORKER SUPPORT A MATTER OF INFLUENCE - Robinson, J. (University of Jaffna, 2016)
Over the last few decades, the literature on corporate repatriation has stressed the importance of effective management of repatriation and has highlighted the fact that unsuccessful management of repatriation leads to employees suffering from problems of adjustment which result in stress and loss of motivation at work. Literature highlights that coworker support help employees to get rid of their stress and establish certainty in an uncertain environment. However, co-workers' influence on repatriation adjustment has apparently been neither discussed nor empirically tested among academic repatriates so far. Given that, in this study researcher aims to find out the impact of academic repatriates' perceived co-worker support on repatriation adjustment. Data was collected from 102 Sri Lankan academic repatriates who had been attached to a foreign university or academic institution for more than one-year, had been involved in academic activities, and, at the survey date, had returned within the past four years. The data was analyzed using appropriate statistical tools. This study found that repatriates' perceived co-worker support had a positive impact on repatriation adjustment. Further, this study found repatriates' personal and situational variables has an influence on co-worker support but not on adjustment. The overall findings underline the essential role of co-worker in the adjustment process of academic repatriates. An in-depth discussion of findings, contributions, limitations, and implications for further research are presented.
Keywords: Repatriation; Adjustment; Co-worker support; Academics